2022
DOI: 10.1021/acs.jpcb.2c00557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concentration and Temperature on the Structure and Ion Transport in Diglyme-Based Sodium-Ion Electrolyte

Abstract: Glyme-based sodium electrolytes show excellent electrochemical properties and good chemical and thermal stability compared with existing carbonate-based battery electrolytes. In this investigation, we perform classical molecular dynamics (MD) simulations to examine the effect of concentration and temperature on ion−ion interactions and ion− solvent interactions via radial distribution functions (RDFs), mean residence time, ion cluster analysis, diffusion coefficients, and ionic conductivity in sodium hexafluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
2
3
0
Order By: Relevance
“…Classical molecular dynamics (MD) simulation was introduced to explain the unexpectedly high ionic conductivity at the lower temperature region (−30 to −60 °C) (Figure b,c). The PF 6 – anions mainly locate in the outer layer of the solvation sheath, illustrating that a low fraction of contact ion pairs (CIPs) or anion aggregates (AGGs) are formed in the electrolyte with NaPF 6 salt, which is consistent with the Raman spectra (Figure S5) and the previous results. In the typical solvation structure, there are six THF molecules in the solvation sheath for the electrolyte 1 M NaPF 6 -THF (inset in Figure b). In contrast, there are four THF molecules and two MeTHF molecules in the solvation sheath for NaPF 6 -THF/MeTHF (inset in Figure c).…”
Section: Resultssupporting
confidence: 87%
“…Classical molecular dynamics (MD) simulation was introduced to explain the unexpectedly high ionic conductivity at the lower temperature region (−30 to −60 °C) (Figure b,c). The PF 6 – anions mainly locate in the outer layer of the solvation sheath, illustrating that a low fraction of contact ion pairs (CIPs) or anion aggregates (AGGs) are formed in the electrolyte with NaPF 6 salt, which is consistent with the Raman spectra (Figure S5) and the previous results. In the typical solvation structure, there are six THF molecules in the solvation sheath for the electrolyte 1 M NaPF 6 -THF (inset in Figure b). In contrast, there are four THF molecules and two MeTHF molecules in the solvation sheath for NaPF 6 -THF/MeTHF (inset in Figure c).…”
Section: Resultssupporting
confidence: 87%
“…The RDFs exhibit a maximum at 2.35 Å for Na + −O interactions, indicating that the sodium ion is surrounded by DG molecules as the first solvated sheath. The calculated coordination number (CN) of Na−O in 0.5M‐D (2.18) is higher than that in 1M‐D (1.99), and it further increases to 2.26 at −30 °C, which supports the conclusion that more DG enters the solvated sheath [13] …”
Section: Resultssupporting
confidence: 64%
“…The calculated coordination number (CN) of NaÀ O in 0.5M-D (2.18) is higher than that in 1M-D (1.99), and it further increases to 2.26 at À 30 °C, which supports the conclusion that more DG enters the solvated sheath. [13] To gain insight into the practicality of 0.5M-D in subzero environments, LMNM'T//Na half cells were assembled to estimate the electrochemical performance, and the common electrolyte 1M NaPF 6 in propylene carbonate with 5 vol. % fluoroethylene carbonate (denoted as PC) was chosen as a comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Based on their analysis, they found that a change in the solvent concentration can suppress the anion-cation contribution to conductivity and increase the Li + transference number [29]. Similarly, the effect of concentration and temperature on the ion transport in diglyme-based sodium ion electrolyte were reported by Ardhra et al [30]. They showed that the ionic correlations have to be considered to correctly predict the experimentally observed trends in ion conductivity.…”
Section: Introductionmentioning
confidence: 84%